Modeling and Visualization of Artillery Fire Formation based on Target Coordinates in The Forward Observer Simulator - Fery Prasetyanto; Bambang Pudjoatmodjo; Agi Dwi Putra Sembiring M; Naufal Fahim Murran; Fenica Salsabila Malsyasila; Nabilah Farrassyajidah Arrosyid (IJAIT (International Journal of Applied Information Technology), 2021)
The Forward Observer (FO) role is vital in military operations, especially in the Medan Artillery unit. FO was in charge of directing artillery fire against the target. In the execution of artillery fire, several types of artillery fire formations are often carried out to hit the target correctly. The formation includes Tama, Tamu, Seka, Seki and Lingkar. In the FO simulator, the artillery fire formation is modeled and visualized in 3D. Modeling and visualization of artillery fire formation can save costs for military operations training in the Medan Artillery unit. In the test results, by entering several parameters, the formula has succeeded in modeling the type of artillery fire according to the type of formation.